Solvent-Free Aerosol Deposition for Highly Luminescent and Thermally Stable Perovskite-Ceramic Nanocomposite Film - Kim, Sunghoon; Cho, Myung Yeon; Kim, Ik Soo; Kim, Won Jung; Park, Sung Han; Baek, Seungmin; Oh, Jong Min; Kim, Sang Wook (Advanced Materials Interfaces, 2019)
Luminescent perovskite structure has been used in a polymer-encapsulated form for display applications. However, insulating polymers as a host matrix are intrinsically vulnerable to thermal stresses which cause softening distortion or deterioration in thermoplastic polymers. Here, nanostructured CsPbBr3/Al2O3 composite film is developed by aerosol deposition method. At first, CsPbBr3/Al2O3 composite powders with bright and saturated green emission are synthesized. Then, the ceramic composite powder comprising monoclinic CsPbBr3 nanocrystals supported on submicron α-Al2O3 particles is successfully transformed to a film-type by aerosol deposition, which enables a nonsolvent-induced process at room temperature. The deposited films show a pure green spectrum with a narrow full width at half maximum of 17 nm, high long-term stability at 150 °C for over 20 d, and an absolute photoluminescence quantum yield of 8%–15%. In general, inorganic films are known to have difficulty with flexibility and patterns. However, the deposited film can be employed in useful applications such as down-converting materials for an LCD backlight with a wide-color gamut of 89.2% in Rec. 2020, highly flexible ceramic composite films, multilayer films, patterning of surfaces for an advanced color filter array, and deposition on curved substrates toward diverse display fields.
Keywords: Aerosol deposition; Aerosol deposition method; Ceramic composite powders; Display application; Perovskite ceramics; Perovskite structures; Photoluminescence quantum yields; Thermoplastic polymer; aerosol deposition; CsPbBr3/Al2O3 nanocomposite; photoluminescence; thermal stability